2016
DOI: 10.5001/omj.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors for Intravenous Colistin Use-related Nephrotoxicity

Abstract: The use of colistin is relatively safe for patients that have normal renal functions. However, better standardization of the definition of nephrotoxicity in those patients with the use of scoring systems and close monitoring are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…A. baumanni was observed to be the causative microorganism in all patients, and the most frequent infection was pneumonia. Similar to our study, it was determined that A. baumannii is the most common agent in other studies [ 8 , 18 , 22 ], and the most frequent infection is pneumonia [ 8 , 12 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A. baumanni was observed to be the causative microorganism in all patients, and the most frequent infection was pneumonia. Similar to our study, it was determined that A. baumannii is the most common agent in other studies [ 8 , 18 , 22 ], and the most frequent infection is pneumonia [ 8 , 12 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Nephrotoxicity ratios differ in studies conducted on the subject, and it is thought that this difference may be due to different patient populations and the use of different criteria. In recent years, for obtaining more standardized data, varying criteria have been used, and the RIFLE criteria provide a useful framework for nephrotoxicity [ 8 , 14 ]. Ricci et al [ 15 ] defined the RIFLE classification as a simple, readily available clinical tool to classify AKI in different populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were also similar to the results from previous reports. According to Koksal I, age was positively correlated with nephrotoxicity 10 . The majority of patients in this study population aged 60 or over and nephrotoxicity was observed in 41.8% of patients in this group while only 19.2% of patients under-60 experienced the event.…”
Section: Discussionmentioning
confidence: 99%
“…and risk factors for renal damage caused by Colistin. Factors associated with renal damage were old age, high levels of Creatinine, diabetes, and chronic obstructive pulmonary disease (41). Binh and colleagues (2015) reported a 67.9% success rate when treating patients with Colistin.…”
Section: Introductionmentioning
confidence: 99%